Association between type 2 diabetes mellitus and Helicobacter pylori infection - Abdulbari BENER; Rosetta MICALLEF; Mustafa AFIFI; Moutaz DERBALA; Hamad M. AL-MULLA; M. Asad USMANI (Turkish Journal of Gastroenterology, 2019)
-